Hydroethanolic Allium sativum extract accelerates excision wound healing: evidence for roles of mast-cell infiltration and intracytoplasmic carbohydrate ratio - Mohammad Reza Farahpour; Saeed Hesaraki; Darab Faraji; Rasoul Zeinalpour; Mohammad Aghaei (Universidade de São Paulo, 2017)
ABSTRACT The present study was designed to evaluate the in vivo effect of Allium sativum (garlic) hydroalcoholic extract on wound healing in rats. For this purpose, 72 mature Wistar rats were divided into four groups (n=18/each) to receive no treatment, placebo, Cicalfate(r), or 2% Allium sativum (AS) extract, administered topically to the wound area, for 21 days. Following the experimental period, tissue samples were dissected out and underwent to histopathological analyses. Fibroblasts, fibrocytes, mast cells, intra-cytoplasmic carbohydrate ratio, neovascularization, collagen deposition, and re-epithelialization were analyzed in all groups. Animals in the treated groups showed significant enhancement in fibroblast, fibrocyte, and mast-cell distribution. Significantly higher neovascularization was observed on day 3 after wound induction in AS-treated animals versus those in the placebo, Cicalfate, and untreated groups (P<0.05). A dose-dependent, significantly higher intra-cytoplasmic carbohydrate storage was observed in treated animals. Our data show that AS promotes wound healing due to its preliminary impact on mast-cell distribution, which enhanced collagen synthesis and upregulated angiogenesis, and shortened the healing process by enhancing the intra-cytoplasmic carbohydrate ratio.